Alginate-templated synthesis of CoFe/carbon fiber composite and the effect of hierarchically porous structure on electromagnetic wave absorption performance. (October 2019) - Song, Zhiming; Liu, Xiaofang; Sun, Xin; Li, Ya; Nie, Xiaoyu; Tang, Wukui; Yu, Ronghai; Shui, Jianglan
Abstract: Natural alginate fibers are used as templates to fabricate CoFe alloy-decorated hierarchically porous carbon fibers (HPCFs). Due to the coordination with negatively charged α−L−guluronate blocks, transition metal (TM) ions could be confined in the "egg box" structure of alginate, which convert to CoFe alloy particles that homogenously embedded in HPCFs during carbonization. The composition and weight ratio of magnetic particles could be well controlled by adjusting the absorbed TM ions and carbonization temperature. Unlike previous analogues with uniform mesopores, this composite fiber simultaneously possesses a number of mesopores and a high proportion of submicron macropores which not only facilitates the accommodation of large-sized CoFe particles, but also induces abundant interfacial polarization and EMW multi-scattering. Remarkably, the CoFe/HPCF with a filler loading as low as 15 wt% in matrix achieves an extremely strong reflection loss of −69.1 dB at a thin thickness of 1.6 mm, and its effective absorption bandwidth reaches 5.2 GHz, showing better comprehensive properties than other similar absorbers. This work highlights the importance of hierarchically porous structure (especially macroporous structure) on improving EMW absorption. The synthetic strategy is green, low cost, scalable, and can be used to synthesize other highly efficient composite absorbers. Graphical abstract: Image 1